Penerapan Sanksi Pidana Terhadap Pelaku Tindak Pidana Pembunuhan Yang Dilakukan Oleh Anak - Risky Themar Bes Safsafubun; Hadibah Zachra Wadjo; MARGIE GLADIES SOPACUA (Faculty of Law Pattimura University, 2022)
Introductioan: This article analyzes the application of appropriate criminal sanctions against children as perpetrators of the crime of murder.Purposes of the Research: The purpose of this article is to clarify the application of appropriate criminal sanctions against children as perpetrators of the crime of murder. Methods of the Research: This article uses a normative writing method with an analytical descriptive approach. Results of the Research: Decision number 8/Pid.Sus-Anak/2018/PNAmb Son of Irawan Alias Iwan is proven legally and convincingly guilty of committing a criminal act of Deliberately Taking the Life of Another, as regulated in Article 338 of the Criminal Code; Sentencing the child Irawan Alias Iwan in the form of imprisonment for 5 (five) years reduced as long as the child is temporarily detained, with an order to remain detained. As for Article 71 paragraph (5) of Law No. 11 of 2012 stipulates: further provisions regarding the form and procedure of criminal execution as referred to in paragraph (1), paragraph (2), and paragraph (3) shall be regulated by a Government Regulation. Similarly, the provisions contained in Article 82 paragraph (4) of Law no. 11 of 2012 states: further provisions regarding actions as referred to in paragraph (1) shall be regulated by a Government Regulation.